Characteristics of lymph node (No.5 and No.6) metastasis and significance of lymph node dissection in Siewert type II esophagogastric junction adenocarcinoma (AEG): No.5 and No.6 lymph node metastases of AEG and clearance. Issue 35 (3rd September 2021) - Zhang, Xu; He, Xiao-dong; Zhang, You-cheng; Yang, Ke-hu; Tian, Jin-hui; Chen, Yao-long
Abstract: Background: To analyze the characteristics, related risk factors, and prognosis of lymph node metastasis (Number [No.] 5 and No.6) in the group of adenocarcinoma of esophagogastric junction (AEG). Methods: The patients with Siewert II AEG who underwent total gastrectomy and D2 lymph node dissection from September 2015 to December 2018 in Lanzhou University Second Hospital were enrolled in this study. The pathological features of the postoperative specimens were analyzed (sex, age, maximum diameter, location, depth of invasion, degree of differentiation, neurological and vascular invasion, etc), and the lymph node metastasis rate of No.5, No.6 groups were calculated. The analysis was performed by IBM SPSS statistical software. The risk factors associated with lymph node metastasis in No.5 and No.6 groups were analyzed. Survival analysis was performed by Kaplan-M method, and survival rate was estimated, Log-rank test was used for comparison, and the difference was statistically significant at P < .05. Results: There were 142 cases of Siewert type II AEG with the positive rate of No.5 lymph nodes being 10.81% (8/74), and the positive rate of No.6 lymph nodes was 8.33% (11/132). No.5 and No.6 lymph nodes metastasis were not associated with gender, age, tumor maximum diameter, location (cardiac left/cardiac right) ( P > .05), and were associated with invasion depth, differentiation degree, nerve and vascular invasion ( P < .05). In the No.5 lymph node-positive group, the 3-year Overall Survival (OS) was 25.0%, and the No.5 lymph node-negative group had a 5-year OS of 57.8%, which was statistically different ( P < .05). The 3-year OS was 18.2% in No.6 node-positive group and 53.8% in No.6 node-negative group, and the difference was statistically significant ( P < .05). Conclusion: For Siewert type II AEG, the lymph node metastasis rate was higher in No.5 and No.6 groups when the tumor invaded all layers of gastric wall and was poorly differentiated complicated with vascular nerve invasion, and the lymph node metastasis rate was lower at 3 years, which may be more appropriate for total gastrectomy +D2 lymph node dissection.